Osteological ontogeny and malformations in larval and juvenile golden pompano Trachinotus ovatus (Linnaeus 1758). (1st October 2014) - Zheng, Panlong; Ma, Zhenhua; Guo, Huayang; Zhang, Dianchang; Fu, Mingjun; Zhang, Nan; Jiang, Shigui
Abstract: The osteological ontogeny and the incidence of deformities occurred in vertebral column and caudal complex were studied from 1 day post hatch (DPH) to 31 DPH in Trachinotus ovatus . Results indicate that the development of both caudal complex and vertebral column initiated between 7 DPH and 9 DPH along with the calcification of haemal arches and neural arches, and occurrence of caudal elements. The last element of caudal complex, uroneural, appeared on 18 DPH. A high number of malformations in the vertebral column and caudal complex were detected in this study. More than 33% experimental fish exhibited at least one type of malformation. Results from this study provide the first reference on the osteological ontogeny and malformation of golden pompano. Such information can be applied to the quality control for fingerling production in golden pompano.